The development of a CBT-informed approach to supporting type 2 diabetes self-management - Elné Visagie; Elné Visagie; Elmari Deacon; Rümando Kok; Rümando Kok (Frontiers in Clinical Diabetes and Healthcare)
BackgroundThe self-management of adults with type 2 diabetes proves to be a continuous challenge. Within the South African context, socio-economic disparities, unequal access to healthcare and varying healthcare beliefs augment these challenges. CBT is a time-sensitive and structured intervention that has been effectively implemented for chronic diseases. CBT has been employed to improve psychological outcomes in adults with type 2 diabetes, but there is limited research on how this therapeutic intervention can enhance self-management outcomes of type 2 diabetes. Adaptable CBT-based interventions are needed to promote a holistic approach to type 2 diabetes self-management and empower a broader range of healthcare professionals to provide targeted interventions. Flexible interventions can promote patient engagement and be integrated into various healthcare settings where patients already access services.MethodThe study employed document analysis to develop CBT-informed guidelines. Data was analysed by means of content analysis. Two research studies formed the dataset, and categories and subcategories were identified. The categories were integrated and used to develop the CBT-informed guidelines.ResultsThese guidelines were based on core CBT components and divided into the introduction, working, and consolidation phases. The guidelines specified the roles of healthcare practitioners who would implement them and provided skills and techniques for healthcare professionals and patients within each phase.ConclusionThe CBT-based interventions aimed to provide a tool for healthcare practitioners and patients in terms of flexibility, accessibility, and personalisation.